What to Expect as Corn Yields Face a Third Straight La Niña - Colussi, Joana; Schnitkey, Gary; Cabrini, Silvina María (University of Illinois, 2022)
Meteorologists are forecasting a third consecutive year of La Niña. The occurrence of two successive La Niña winters in the Northern Hemisphere is common, however, having three in a row is relatively rare. A triple La Niña has happened only twice since 1950. The last time La Nina was in place for three years in a row was from 1999 to 2001. But what could this mean for corn production in Brazil, the United States, and Argentina? In the previous article, we presented descriptive analyses of deviations from the trendline of soybean yields over the last 30 years (see farmdoc daily, May 23, 2022). In this article, we made the same analysis to evaluate corn yields in the aforementioned countries. La Niña is expected to weaken but persist through the Northern Hemisphere summer and into early winter 2022-23.